ICTD Research in Latin America: literature review, scholar feedback, and recommendations. Issue 4 (1st October 2020) - Stratton, Caroline; Nemer, David
ABSTRACT: Reviews of the ICTD literature have noted a scarcity of studies about Latin American countries. We investigate (1) what are the alternatives to ICTD and English-language ICTD publication venues researchers utilize to disseminate their work and why they may do so, and (2) what methodological, theoretical, and contextual characteristics these researchers bring to their publications. The study takes a two-pronged approach to answer these questions: a survey of researchers who have conducted ICTD research in Latin America and an analysis of their ICTD publications. We find that researchers use an array of specific alternative and additional terms to describe ICTD research, that methodological and theoretical characteristics of the literature resemble ICTD in general, and that contextual coverage of the region is lacking. Our results prompt a set of recommendations for better incorporating scholarship about Latin America in the ICTD field as well as improving global coverage of the ICTD community.